A process management benchmarking model for higher education institutions - Mendonça, Matheus de Melo; Carmo, Breno Barros Telles do; Queiroz, José Eric da Silva; Barreto, Lívia Rodrigues (Revista de Administração da UFSM, 2023)
Purpose: This research presents a multicriteria benchmarking participatory model able to classify Federal Higher Education Institutions (FHEIs) into three levels of process management maturity. Design/methodology/approach: The research was conducted into three stages: (i) assessment model development using the Delphi technique, (ii) data collection through a self-assessment process, and (iii) classification of the FHEIs using PROMSORT. Findings: The results showed that, regardless of the adoption of an optimistic or pessimistic perspective, most FHEIs (51.6% in the optimistic perspective and 54.8% in the pessimistic one) were classified as regular. It is also noteworthy that approximately 80% of the research participating FHEIs maintained their classifications in the sensitivity analysis. Among the six alternatives that presented classification variations, only three varied significantly, confirming the results obtained stability. Research limitations/implications: The use of a participatory approach promotes a consistent benchmark in terms of indicators and metrics to measure performances. Practical implications: PROMSORT provided flexibility to the model, since it is possible to modify the parameters and thresholds in order to adjust the model strictness. Originality/value: The development of a model through which the Federal Higher Education Institutions (FHEIs) can be continually evaluate their process management maturity level.